Paddling time parameters and paddling efficiency with the increase in stroke rate in kayaking. Issue 10 (26th November 2022) - Gomes, Beatriz B.; Ramos, Nuno V.; Conceição, Filipe; Sanders, Ross; Vaz, Mário; Vilas-Boas, João Paulo
ABSTRACT: The paddling stroke rate (SR) is one of the key determinants of flat water kayak performance. The aim of this study was to analyse the way in which the kayak paddler changes the duration of the water and aerial phases due to the increase in stroke rate. Ten elite kayak paddlers (five males and five females) were analysed performing 200 m on-water trials in an individual kayak (K1), at four different stroke rates (60, 80, 100 strokes per minute and race pace). The duration of the water and aerial phases, SR and impulse were computed based on the data collected using the FPaddle system. Results corroborate the importance of reaching higher SR to increase kayak velocity ( r = 0.904, p < 0.001). Both water and aerial phase durations correlated negatively with SR ( r = −0.929, p < 0.001; R = −0.909, p < 0.001, respectively). However, with the first, the correlation was linear ( r 2  = 0.883), and for the second, the trend of relationship was curvilinear ( r 2  = 0.893). Due to differences in correlation, the results suggest that at high SR (above 120 strokes per minute) to continue increasing SR it will be more productive to reduce the duration of the water phase.